Digital-Based Public Service Innovation: Systematic Literature Review - S. Uloli, Merlan; Lahusin, Azwar (West Science Interdisciplinary Studies, 2023)
Previous studies show that the development of digital-based public services is a necessity. The aim of this literature research is to identify changes that have occurred in public services. This article comes from a literature review of research articles found via Google Scholar and Semantic Scholar in the last seven years between 2017 and 2023. The results of the literature review show that digital-based public service innovation has a significant positive impact on public service operations and administrative and bureaucratic reform. . In addition, it is important to understand that innovation in digital-based public services requires three key elements: support from government officials, resources including human resources, finance and infrastructure, and benefits obtained by the government. However, there are a number of challenges still being faced, such as technical problems, lack of budget, limited human resources, and the government's inability to adapt to change. Therefore, improvements and expansion of electronic e-government in Indonesia need to continue.